Checklist of helminth parasites in wild carnivore mammals from Brazil - Vieira, Fabiano M.; Luque, José L.; Muniz-Pereira, Luis C. (Zootaxa, 2008)
Ninety-five helminth parasite species totaling 480 records (including 60 new host and geographical records) in 21 species of wild carnivore mammals from Brazil were listed. Nineteen undetermined helminth species and 4 undetermined host species were also included. Information about the site of infection of parasites, localities, references and a host-parasite list were included herein.